Endodontic treatment of a fused maxillary lateral incisor - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 1998)
A case report of endodontic treatment of a maxillary lateral incisor that fused with a supernumerary tooth is presented, The fused maxillary lateral incisor was in supraposition on the maxillary dental arch and required orthodontic treatment, The fused tooth was prepared for endodontic therapy. Cleaning and shaping of the root canals were performed, Then, the Ultrafil technique was used for obturation of the root canals, After orthodontic treatment, the teeth was mesiodistally reduced in size and restored with an anterior composite resin.
Keywords: GEMINATION; TOOTH